Pengaruh Kepribadian, Literasi Keuangan dan Lingkungan Keluarga terhadap Minat Berwirausaha (Business and Accounting Education Journal, 2022)
This study aims to analyze the influence of personality, financial literacy, and family environment on interest in entrepreneurship. This quantitative study has a population of 85 students from HIPMI PT UNNES and a sample of 55 students is taken. Data collection techniques using a questionnaire. Data were analyzed using descriptive analysis and multiple regression analysis. The results of the study revealed that personality, financial literacy, and family environment simultaneously had a significant positive effect on interest in entrepreneurship. Personality has a significant positive effect on interest in entrepreneurship. Financial literacy has no effect on interest in entrepreneurship, family environment has a significant positive effect on interest in entrepreneurship.